Occupational Lifting Tasks and Retinal Detachment in Non-Myopics and Myopics: Extended Analysis of a Case-control Study - Stefano Mattioli; Stefania Curti; Rocco De Fazio; Robin Mt Cooke; Francesca Zanardi; Roberta Bonfiglioli; Andrea Farioli; Francesco S. Violante (Elsevier, 2012)
Objectives: Lifting heavy weights involves the Valsalva manoeuvre, which leads to intraocular pressure spikes. We used data from a case-control study to further investigate the hypothesis that occupational lifting is a risk factor for retinal detachment. Methods: The study population included 48 cases (patients operated for retinal detachment) and 84 controls (outpatients attending an eye clinic). The odds ratios (OR) of idiopathic retinal detachment were estimated with a logistic regression model (adjusted for age, sex and body mass index). Three indexes were used to examine exposure to lifting; 1) maximum load lifted, 2) average weekly lifting, 3) lifelong cumulative lifting. Results: For all indexes, the most exposed subjects showed an increased risk of retinal detachment compared with the unexposed (index 1: OR 3.57, 95% confidence interval [CI] 1.21-10.48; index 2: OR 3.24, 95% CI 1.32-7.97; index 3: OR 2.23, 95% CI 1.27-8.74) and dose-response relationships were apparent. Conclusion: These results reinforce the hypothesis that heavy occupational lifting may be a relevant risk factor for retinal detachment.